Social and economic issues on money and real economy relations : perspectives from Islamic economics and finance - Choudhury, Masudul Alam, 1948- (Humanomics, 2006)
This e-book on Islamic Perspectives of Social Financing brings together selected papers on the nature of the Islamic financial system, the concept of social capital, and thereby of social goods and social money that are part and parcel of the ethical market transformation in the Islamic economy. A paper contrasts the fractional reserve requirement monetary system and its structure based primarily on fiat money with the conception and functions of money in the Islamic economy supported by the gold standard. This perspective beckons the strong case of a return to the gold standard, which prior t.